The Case for Subsidizing Hydroelectricity Development in Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
We should stop using imported energy and have our own source of energy. When we have our own clean form of energy, the government or the developers should not hesitate to promote it. It’s not only our nation’s economy that we will be helping, but also the world environment that we will be protecting. We should find ways to reduce the import of petroleum products and to promote hydropower. Although the new government has shown keen interest in bailing Nepal out of the energy crisis, it needs to act now to bring acts and laws to promote hydropower. No law should be able to stop hydropower being developed. The government should spend on hydropower even if it has to tax petroleum products. It should provide incentives to hydropower developers.Hydro Nepal Journal of Water, Energy and Environment Issue No. 4, January, 2009 Page 40-41